2021
DOI: 10.1080/00913847.2021.1922947
|View full text |Cite
|
Sign up to set email alerts
|

Does wearing a mask while exercising amid COVID-19 pandemic affect hemodynamic and hematologic function among healthy individuals? Implications of mask modality, sex, and exercise intensity

Abstract: Roshan (2021): Does wearing a mask while exercising amid COVID-19 pandemic affect hemodynamic and hematologic function among healthy individuals? Implications of mask modality, sex, and exercise intensity, The Physician and Sportsmedicine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…Since dyspnea was not assessed at baseline in our study, but only during exercise, there was a “condition” main effect, where wearing the facemasks overall resulted in higher dyspnea scores, in spite of the lack of statistically significant interactions between condition and time. In addition, the different conditions of our study did not show relevant differences for O 2 saturation, although a reduction of O 2 saturation was usually observed during the 30-min steady-state test in accordance with other studies using moderate-to-high intensity physical exercises [11, 12, 14-16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since dyspnea was not assessed at baseline in our study, but only during exercise, there was a “condition” main effect, where wearing the facemasks overall resulted in higher dyspnea scores, in spite of the lack of statistically significant interactions between condition and time. In addition, the different conditions of our study did not show relevant differences for O 2 saturation, although a reduction of O 2 saturation was usually observed during the 30-min steady-state test in accordance with other studies using moderate-to-high intensity physical exercises [11, 12, 14-16].…”
Section: Discussionsupporting
confidence: 92%
“…These changes should be studied under exercise at LT intensity for more than 30 min. Regarding external validity, the low number of females must be considered as a limitation due to its possible influence on physiological parameters [16], and future studies should consider a paired matched sample for sex distribution. Despite we tried to get a balanced composition of both sexes (15 males and 15 females) according to the initial sample of the trial protocol (NCT04832893), 11 females did not receive baseline measurements nor the required interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our main modality of testing was the exercise treadmill. This modality of exercise stress was also used by Driver and Ahmadian ( Ahmadian et al, 2021 ), while other studies by Epstein and Egger have used the cycle ergometry exercise test. Earlier studies have shown that exercise treadmill testing typically produces a higher heart rate response compared to cycle ergometry ( Niederberger et al, 1974 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies on heart rate variability with mask use indicated that mask use had no effect on heart rate [ 21 , 23 , 24 ], Li et al reported that the use of N95 affected heart rate variability [ 25 ]. In our study, the HR peak was not different in the masked and unmasked test in females; it was found to be lower in males with mask use.…”
Section: Discussionmentioning
confidence: 99%